Alfa-mannosidosis: Frequent Symptoms in Rare Patient - Nato D. Vashakmadze; Natalia V. Zhurkova; Ludmila K. Mikhaylova; Marina A. Babaykina; Maria S. Karaseva; Kristina V. Pashkova; Ekaterina Yu. Zakharova; Leyla S. Namazova-Baranova (Вопросы современной педиатрии, 2023)
Background. Alfa-mannosidosis is ultra-rare autosomal recessive lysosomal storage disease caused by the mutation in the MAN2B1 gene. Pathogenic nucleotide variants and structural changes in this gene lead to acid alpha-mannosidase deficiency, this enzyme is involved in oligosaccharides degradation. This disease is characterized by multisystem involvement and chronic progressive course.Clinical case description. The clinical case attracted our attention due to the late disease diagnosis in a boy living in a metropolis. The child has classic clinical manifestations of the disease: typical phenotype, spinal deformity, developmental speech and motor delays, hearing loss, hepatomegaly, splenomegaly, umbilical and inguinal hernias. Despite developmental speech delay and frequent recurrent otitis, the patient has not been referred to surdologist examination until the age of 4.5 years. Intriguing fact is the presence of congenital cataract that was the reason for surgery twice.Conclusion. Congenital cataract is one of the early manifestation of this disease. 3 out of 8 patients with alfa-mannosidosis observed in our centre had congenital cataract. We assume that such patients should be referred to genetics for the early exclusion of alpha-mannosidosis. Late diagnosis and progressive course of the disease led to early disability of the patient. Nowadays, as enzyme replacement therapy is available, it is crucial to identify these patients timely in order to improve their quality of life and increase survivability.